Application of TAMSAT-ALERT soil moisture forecasts for planting date decision support in Africa - Black, Emily; Asfaw, Dagmawi Teklu; Sananka, Alex; Aston, Stephen; Boult, Victoria L.; Maidment, Ross I. (Frontiers in Climate, 2023)
Deciding when to plant is critical for smallholders in Africa. If they plant too early, farmers risk seedling death if the rains are not established; if they plant too late, there will not be enough rain to sustain the crop through critical development periods. In this study, we present a new decision support tool (DST) that accounts for the trade-off in the risks of early and late planting through advisories based on both short- and long-range forecasts of crop water availability. Unlike most existing operational systems, which are based solely on rainfall, the DST presented here uses ensemble forecasts of soil moisture to estimate the optimal planting date at a local scale. Evaluations using >30,000 observations of planting date and yield in Kenya, Rwanda, Uganda, Zambia and Malawi demonstrate that that planting at the optimal time would increase yield by 7-10% overall, and up to 20% for late planting farmers. The DST has been piloted by One Acre Fund for the 2019-2020, 2020-2021 and 2021-2022 seasons and there is strong demand for the service to be extended further. We conclude from the evaluations and pilots that the planting date DST has the potential to strengthen farmer decision making and hence their resilience to climate variability and change.